The Bolshevik revolution : 1917-1923 - Carr, Edward Hallett (Harmondsworth : Penguin, 1966)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: bolsjewisme; Russische revolutie; Rusland